HUBUNGAN KEBERSIHAN GIGI DAN MULUT (OHI-S) DENGAN GINGIVAL INDEKS PADA WANITA PUBERTAS SMP NEGERI 2 PANCUR BATU - Rawati Siregar; Sri Junita Nainggolan; Aminah Saragih; Netty Jojor Aritonang (Poltekkes Kemenkes Medan, 2023)
Dental and oral hygiene means a state when the oral cavity include teeth and gum tissue is clean. The actions of cleaning and refreshing the oral cavity, teeth and gums can prevent the transmission of disease through mouth. Dental and oral hygiene (OHI-S) is closely related to the occurrence of gingivitis. The research type used in this study is analytical research with cross sectional method using using Chi-Square Test. The number of the population of this study is 100 people and the sampling technique used purposive sampling, the samples taken are 30 people. The purpose of this study is to find out the relation of dental and oral hygiene (Ohi-S) with gingival index on puberty women. The results showed that the average of debris index were 6 people in good criterion (0,5), moderate criterion 18 people (1,2) and bad criterion 6 people (2,2). The Calculus index defines 6 people (0,4) as good criterion , 15 person (1,4) as moderate criterion and 9 person (2,2) as bad criterion. OHI-S defines the average criteria as follow : 6 people (1,2) as good, 9 people (2,4) as moderate and 16 person (3,6) as bad. Meanwhile, gingival index defines some criteria,1 person (0,9 ) as light, 22 people (1.5) as moderate and 7 people (2,3) as severe. The conclusions of this study is that from the samples, the 30 puberty women, it is found that in average they pay less attention to their oral and dental health. It is expected that the pregnant women should improve their dental and mouth health.